Optimal Coupler Topology for Dynamic Wireless Power Transfer for Electric Vehicle - Karim Kadem; Mohamed Bensetti; Yann Le Bihan; Eric Labouré; Mustapha Debbou (Energies, 2021)
Recently, the number of electric vehicles (EVs) is increasing due to the decline of oil resources and the rising of greenhouse gas emissions. However, EVs have not received full acceptance by consumers due to the limitations of the stored energy and charging problems. The dynamic or in-motion charging solution has become a suitable choice to solve the battery-related issues. Many researchers and vehicle manufacturers are working to develop an efficient charging system for EVs. In order to improve the efficiency of the dynamic wireless power transfer (DWPT), the electromagnetic coupling coefficient between the two parts of the coupler must be maximized. This paper was dedicated to find the optimal topology of a magnetic coupler with the best coupling factor while taking in consideration the displacement and the misalignment of the EV. The article is introduced by developing a methodology for characterizing the electrical parameters of couplers, followed by a comparative study of different forms of coils suitable for dynamic charging of electric vehicles. The particularity of the proposed study concerned the overall dimensions, or the areas occupied by the windings of the coils remaining the same for all the chosen shapes and corresponding to the surface that is actually available under the EV. Simulation and experimental tests were carried out to validate the proposed study.